Eliminating the dose-rate effect in a radiochromic silicone-based 3D dosimeter. (2nd July 2015) - Høye, E M; Balling, P; Yates, E S; Muren, L P; Petersen, J B B; Skyt, P S
Abstract: Comprehensive dose verification, such as 3D dosimetry, may be required for safe introduction and use of advanced treatment modalities in radiotherapy. A radiochromic silicone-based 3D dosimetry system has recently been suggested, though its clinical use has so far been limited by a considerable dose-rate dependency of the dose response. In this study we have investigated the dose-rate dependency with respect to the chemical composition of the dosimeter. We found that this dependency was reduced with increasing dye concentration, and the dose response was observed to be identical for dosimeters irradiated with 2 and 6 Gy min −1 at concentrations of 0.26% (w/w) dye and 1% (w/w) dye solvent. Furthermore, for the optimized dosimeter formulation, no dose-rate effect was observed due to the attenuation of the beam fluence with depth. However, the temporal stability of the dose response decreased with dye concentration; the response was reduced by (62  ±  1)% within approximately 20 h upon irradiation, at the optimal chemical composition and storage at room temperature. In conclusion, this study presents a chemical composition for a dose-rate independent silicone dosimeter which has considerably improved the clinical applicability of such dosimeters, but at the cost of a decreased stability.